2020
DOI: 10.1002/wmh3.378
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Collateral Consequences of Punishment Amidst the COVID‐19 Pandemic

Abstract: Bipartisan governmental representatives and the public support investment in health care, housing, education, and nutrition programs, plus resources for people leaving prison and jail (Halpin, 2018; Johnson & Beletsky, 2020; USCCR, 2019). The Personal Responsibility and Work Opportunity Reconciliation Act of 1996 banned people with felony drug convictions from receiving food stamps or Supplemental Nutrition Assistance Program (SNAP) benefits. Food insecurity, recidivism, and poor mental and physical health out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Moreover, participants also stated the stigma associated with applying for or receiving additional assistance hindered caregivers’ ability to provide for their children, especially during the pandemic. Research has found that shame and anxiety can intensify the stigmatization of participation in food assistance programs and the acceptance of charitable foods [ 61 , 62 ]. Thus, even if resources and services were available in these communities, there is a low participation rate due to a lack of knowledge and the stigma associated with receiving benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, participants also stated the stigma associated with applying for or receiving additional assistance hindered caregivers’ ability to provide for their children, especially during the pandemic. Research has found that shame and anxiety can intensify the stigmatization of participation in food assistance programs and the acceptance of charitable foods [ 61 , 62 ]. Thus, even if resources and services were available in these communities, there is a low participation rate due to a lack of knowledge and the stigma associated with receiving benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In NZL 34 , in 2019, the De-partment of Corrections started a program with the government on housing for the released. In the U.S., some states revised the rules of access to the food security program to allow the concession to released inmates 45 .…”
Section: Category 3 -Mitigating the Consequences Of The Pandemic And ...mentioning
confidence: 99%
“…Na NZL 34 , desde 2019, o Departamento de Correções iniciou um programa com o governo de habitação para egressos. Nos EUA, alguns estados revisaram as regras de acesso ao programa de segurança alimentar para permitir a concessão aos egressos do sistema prisional 45 .…”
Section: Catunclassified